Andrienko T. P. Strategies of translating foreign inclusions in character speech in belles-lettres - Andrienko T. P. (Philological Treatises, 2020)
The role of translation strategies and procedures in rendering of foreign inclusions in characters’ speech is studied, the potential of each strategy in representing speech characteristics and author’s discourse is defined